2004
DOI: 10.1007/s00468-004-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Norway spruce (Picea abies) seedlings from repeated drought as affected by boron nutrition

Abstract: The effects of two boron (B) levels on growth, shoot water potential, gas exchange and nutrient accumulation in Norway spruce [Picea abies (L.) Karst.] seedlings were studied in a growth room experiment lasting 22 weeks which included well-watered control seedlings and seedlings exposed to one (8 days) or two (6+8 days) periods of drought and a rewatering period (8 days) at the end of the experiment. The effects of B and drought were monitored during drought and recovery. Needle B concentrations were 6 mg kg −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…However, the role of B in increasing drought tolerance has also been observed in different species (Möttönen et al, 2005;Hodecker et al, 2014;Pita-Barbosa et al, 2016). Our previous studies confirmed the great influence of B on the increase of root growth and water use efficiency in Eucalyptus urophylla (Hodecker et al, 2014).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, the role of B in increasing drought tolerance has also been observed in different species (Möttönen et al, 2005;Hodecker et al, 2014;Pita-Barbosa et al, 2016). Our previous studies confirmed the great influence of B on the increase of root growth and water use efficiency in Eucalyptus urophylla (Hodecker et al, 2014).…”
Section: Introductionsupporting
confidence: 73%
“…Similarly, to other nutrients, the importance of Ca and/or B for drought tolerance of plants has been shown in several studies (Möttönen et al, 2005;Hassan et al, 2011;Barros Filho, 2014;Hodecker et al, 2014;Pita-Barbosa et al, 2016). For clone PL040, although efficient in Ca and B use under sufficient water supply, AE and UE were strongly affected under drought stress, compared to the other genotypes.…”
Section: Responses In Growth Traits As Indicators Of Drought Tolerancmentioning
confidence: 99%
“…In Norway spruce seedlings, a relatively mild drought treatment increased root B concentrations in all B treatments, while needle B was not affected (Möttönen et al, 2001a). After repeated drought treatments, B concentrations decreased in needles; suggesting that translocation to needles was more impaired by stomatal closure than uptake to roots in Norway spruce seedlings (Möttönen et al, 2005). In a survey of Norway spruce stands in Finland, the foliar B concentrations were positively correlated with the occurrence of peatland mosses (Tamminen and Saarsalmi, 2004).…”
Section: Soil and Meteorological Factors Affecting B Uptakementioning
confidence: 96%
“…Similarly, B had little effect on the recovery of Norway spruce seedlings from a drought treatment as indicated by photosynthesis and water relations, but seedlings with high B grew somewhat better after drought. Only seedlings in the most severe drought treatment with low B (6 mg kg −1 in needles) had occurrences of tip dieback (Möttönen et al, 2005). In these cases, the actual damage was apparently caused by acute B deficiency in the growing point, as the drought would reduce water and boron translocation.…”
Section: Drought Resistancementioning
confidence: 99%
“…Induced drought stress leading to changes was more pronounced in Norway spruce seedlings grown under artificial conditions, whether it was a decrease of mycorrhizal colonization in seedlings as soon as exclusion of irrigation for 9 days (Möttönen et al, 2001), 6 days and subsequent 8 days (Möttönen et al, 2005) or 2-4 months in the third and the fifth year (Nilsen et al, 1998). The effect of drought on mycorrhizal colonization within Norway spruce stands (including our study) was not so apparent.…”
Section: Discussionmentioning
confidence: 43%